Generative and Participatory Parametric Frameworks for Multi-player Design Games - Henriette Bier; Yeekee Ku (Footprint)
Generative design processes have been the focus of current architectural research and practice largely due to the phenomenon of emergence explored within self-organisation, generative grammars and evolutionary techniques.